PENERAPAN ROLE PLAYING DALAM MENINGKATKAN KETERAMPILAN BERBICARA DAN KEPERCAYAAN DIRI SISWA SEKOLAH DASAR - Anisa (Jurnal Komunikasi, 2026)
This study aims to determine the application of the role playing method in improving speaking skills and self-confidence of elementary school students. The role playing method is a learning method that allows students to play certain roles in a situation so they can practice speaking, express their opinions, and show themselves more confidently. This study used a classroom action research method with stages of planning, action, observation, and reflection. The data were collected through observation and documentation during the learning process. The results show that the role playing method can make students more active in speaking and more confident when performing in front of the class.